(untitled) (Environment & Health, 2020)
Objective:We carried out aprognostic evaluation of the features of the course of psychophysiological and mental adaptation of pupils and students of modern educational institutions in the context of the implementation of the complex assessment of the quality of life. Materials and methods: The research was conducted on the basis of modern educational institutions in Ivano-Frankivsk. We used hygienic, psychophysiological, psychodiagnostic, and medico-sociological methods of research. Results:During the analysis of intrasystem relationships among separate components of the leading features of the quality of life, it was found that among the young girls their largest number was typical for the scales of Bodily Pain (BP), Vitality (VT), Mental Health (MH), General Health (GH) and Role-Emotional (RE), at the same time, the smallest number according to the scales of Role-Physical (RP), Physical Functioning (PF) and, especially, Social Functioning (SF); among the young boys the largest number of the components was typical for the indicators of the scales of Physical Functioning (PF), Mental Health (MH), Vitality (VT), Bodily Pain (BP), at the same time, was the smallest for the indicators of the scales of General Health (GH), Social Functioning (SF), Role-Physical (RP) and, especially, Role-Emotional (RE).While determining the intersystem relationships between the components of quality of life and the indicators of psychophysiological functions and personality traits, it was found that the closest connection was observed among the indicators of quality of life according to the scales of General Health (GH), Physical Functioning (PF), Social Functioning (SF), Mental Health (MH) by such characteristics of psychophysiological adaptation as a speed of simple and differentiated visual-motor response, mobility and balance of nervous processes, critical frequency of fusion of light blinks, coordination of movements, such characteristics of mental adaptation as neuroticism, situational and personal anxiety, asthenic and depressive states, level of subjective control. Conclusions: In the course of the research the prognostic evaluation of the features of the course of psychophysiological and mental adaptation of pupils and students of modern educational institutions in the context of the implementation of complex assessment of quality of life was made, and the features of intrasystem and intersystem connections between the individual components of quality of life and the indicators of psychophysiological functions and personality traits of the young boys and girls were determined.